x-3/4-2=x-2/3

Simple and best practice solution for x-3/4-2=x-2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3/4-2=x-2/3 equation:


x in (-oo:+oo)

x-(3/4)-2 = x-(2/3) // - x-(2/3)

x-x-(3/4)+2/3-2 = 0

x-x-3/4+2/3-2 = 0

-25/12 = 0

x belongs to the empty set

x belongs to the empty set

See similar equations:

| 5.3x+4=4.3x | | 34=5x+16x^2 | | 6x-(-3x+9)=(x-7)-4(9x-9) | | (4x-9)/(7x^2+9) | | 5[x]=45 | | 5n+1=5(n-1) | | 8(k+11)-6k=9 | | 3u+4=22 | | 16x^2+5x=0 | | 7x+21=2x+56 | | 20y^2-15y^3= | | 1/4(x-3)=1/3(x-2) | | f(x)=5-.2x | | c/8+230/8=200 | | 22/1 | | 5r^2-16r+12= | | -5y-9=4y+2 | | 3k+34=4(6+3k)+1 | | -6-(-2n)=3-6+5 | | 15-2x=-19 | | .11x-.03(40000-x)=760 | | 5d+11=8d-7 | | 3x-2y+5y-8x= | | -2(x-5)-3x=120 | | (57/2)x=26.8 | | -2.3-5x-4.1-3x=-7x+1.6 | | 2(3m-4)=8m-11 | | -2(-2)+4(4)=8 | | -3(2x+4-3-6x)-2=10x | | i+i+1+i+2=228 | | -5/2-1/4 | | .04(2-q)=0.2(q+7) |

Equations solver categories